POST-PARTURIENT UTERINE PROLAPSE IN A BITCH - A CASE STUDY - DEORI, S; SARKAR, M; DEBNATH, S; DAS, G K; SHANKER, UMA (The Indian Journal of Animal Reproduction, 2023)
A rare case of post partum complete uterine prolapse and its successful management in a bitch is reported in this communication.
Keywords: Bitch; Uterine prolapse